Pendampingan Peningkatan Pemberdayaan Masyarakat SD ALMADANY kelurahan Prambangan Kabupaten Gresik Melalui Pelatihan Literasi Keuangan dan Kesehatan Mental Guru - Akhirruddin, Anita; Kirono, Indro (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Mental health is a problem that needs to be taken seriously. Mental health is often experienced by people aged 15 years and over, so it is necessary to address this by knowing the problems and characteristics of people around us who experience mental disorders. Teacher are among those who can experience mental health problems due to their dual role, namely wife, and career. The dual role played by teachers does not rule out possibility of causing stress and depression. Stress and depression need to be handled appropriately and identified as early as possible, for this reason it is necessary to understand the importance of mental health literacy for teachers so that they can work well in educating their students. So in this service the service team want to provide training to Almadany Elementary School teachers on how to recognize the symptoms of mental disorder, as well as how to overcome them both from a psychological aspect and a religious approach.